Acute Cytotoxic and Vasogenic Edema after Subarachnoid Hemorrhage: A Quantitative MRI Study - Weimer, J.M.; Jones, S.E.; Frontera, J.A. (American Journal of Neuroradiology, 2017)
BACKGROUND AND PURPOSE: The mechanism of early brain injury following subarachnoid hemorrhage is not well understood. We aimed to evaluate if cytotoxic and vasogenic edema are contributing factors.MATERIALS AND METHODS: A retrospective analysis was conducted in patients with SAH undergoing diffusion-weighted MR imaging within 72 hours of onset. Apparent diffusion coefficient values derived from DWI were evaluated by using whole-brain histograms and 19 prespecified ROIs in patients with SAH and controls with normal findings on MRI. Cytotoxic edema observed outside the ROIs was assessed in patients with SAH. The average median ADC values were compared between patients with SAH and controls and patients with SAH with mild (Hunt and Hess 1–3) versus severe early brain injury (Hunt and Hess 4–5).RESULTS: We enrolled 33 patients with SAH and 66 controls. The overall average median whole-brain ADC was greater for patients with SAH (808 × 10−6 mm2/s) compared with controls (788 × 10−6 mm2/s, P < .001) and was higher in patients with SAH across ROIs after adjusting for age: cerebral gray matter (826 versus 803 × 10−6 mm2/s, P = .059), cerebral white matter (793 versus 758 × 10−6 mm2/s, P = .023), white matter tracts (797 versus 739 × 10−6 mm2/s, P < .001), and deep gray matter (754 versus 713 × 10−6 mm2/s, P = .016). ADC values trended higher in patients with Hunt and Hess 4–5 versus those with Hunt and Hess 1–3. Early cytotoxic edema was observed in 13 (39%) patients with SAH and was more prevalent in those with severe early brain injury (87.5% of patients with Hunt and Hess 4–5 versus 24.0% of those with Hunt and Hess 1–3, P = .001).CONCLUSIONS: Age-adjusted ADC values were globally increased in patients with SAH compared with controls, even in normal-appearing brain regions, suggesting diffuse vasogenic edema. Cytotoxic edema was also present in patients with SAH and correlated with more severe early brain injury.EBIearly brain injuryHHHunt and Hess